CONDITION OF CORAL REEF, SEAGRASS AND MANGROVE IN TOURISM GARDEN OF TIWORO STRAIT, WEST MUNA REGENCY, SOUTHEAST SULAWESI - Hamsir, Muh; furkan, Al; Izas, Fajar; Agam, Adiyaat Ridho; Jaya, Fitra (Jurnal Ilmu Kelautan SPERMONDE, 2018)
The biodiversity of the Tiworo Strait Conservation Area (KKLD) was highly potential to be developed. However, in recent years, potential utilization has begun to lead to environmental destruction due to the use of destructive fishing gear. Therefore, biophysical studies were needed to give an overview and outlook about the area in order to provide information on the condition of coral reefs, reef fish, mangrove, sea grass, scare/endemic biota and socioeconomic conditions as well as the cause of aquatic ecosystems destruction. The method used to collect the data in the field is by undertaking observation, interview, and literature study method. Observation of coral cover and benthos used was by Point Intercept Transect (PIT) method while for the reef fish, the method used was a visual water census (UVC). Quadratic transect method was used for observation of sea grass and mangrove ecosystem. Meanwhile, the socio-economic condition is done by interview survey technique. The observation result shows the coral condition of the Tiworo Straits KKLD was in the medium category with the mean percentage of live coral of 46%. The lowest percentage of live coral was located at Station 1 of Mandike Island (18%), and the highest was at the Indo Island Station (76%), which is categorized as very good. The number of individual reef fish is 1.217 individuals / m2, and benthos type that dominates was sea urchin. The highest density of mangrove trees was 4000 trees/ha and the lowest was 200 trees/ha. The types of sea grasses observed were Thallasia hemprichi and Ehalus acroides. People, in general, have a livelihood as a fisherman with gill net fishing gear and fishing platform.